Pengaruh Tingkat Suku Bunga dan Nilai Tukar Terhadap Investasi di Provinsi Jambi - Setia Panjaitan (Universitas Batanghari Jambi, 2020)
In this study researchers examined the effect of interest rates and exchange rates in Jambi Province 2000-2019. The purpose of this study is to know: (1) To know and analyze the development of investment, interest rates and exchange rates in the province of Jambi 2000-2019. (2) To determine and analyze the effect of interest rates and exchange rates partially and simultaneously on investment in Jambi Province 2000-2019. The research method use in this research is quantitative descriptive using secondary data. The data used in this study were obtained from relevant agencies. The analytical tools used in this research is multiple linear regression analysis. Based on the silmutaneous testing (F test), its is know that F count (83,014) is greater than F table (3,59), this means that simultaneously there is a significant relationship between the independent variables (interest rates and exchange rates) on the dependent variable (investment). For partial testing (t test), it is concluded that the value is smaller than the t table on the independence variable (-5,474 < 2,109). And on the exchange rate variable t count is greater than t table (7,818 > 2,109).The conclusion obtained in this multiple linear regression analysis is that the interest rate and the exchange rate simultaneously have a significant effect on investment in Jambi Province. Where together the two independent variables have an effect of 90,7% on investment. Partially the interest rate variable has a negative and significant effect on investment in Jambi Province. And the exchange rate variable partially has a positive and significant effect on investment in Jambi Province.